2021
DOI: 10.21203/rs.3.rs-1097336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of the Elevated Thrombosis Risk of Males to the Excess Male Mortality Observed in COVID-19: An Observational Study

Abstract: Background: The mortality rate of COVID-19 is elevated in males compared to females.Objective: Determine the extent that the elevated thrombotic risk in males relative to females contributes to excess COVID-19 mortality in males.Design: Observational study.Setting: Data sourced from electronic medical records from over 200 US hospital systems.Participants: 60,877 patients hospitalized with COVID-19.Exposure: Exposure variable: biological sex; key variable of interest: thrombosis.Main outcome measures: Primary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several studies have attempted to quantify mortality related to thromboembolic events in COVID-19 patients. One study found that COVID-19 patients with a thromboembolic event had a 40% mortality rate, over twice that of COVID patients without a thrombotic event[ 44 ]. Another study, a meta-analysis of 8271 patients, found that patients with COVID-19 who had thromboembolic events had a pooled mortality rate of 23%, with thromboembolism significantly increasing the odds of mortality by as high as 74%[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to quantify mortality related to thromboembolic events in COVID-19 patients. One study found that COVID-19 patients with a thromboembolic event had a 40% mortality rate, over twice that of COVID patients without a thrombotic event[ 44 ]. Another study, a meta-analysis of 8271 patients, found that patients with COVID-19 who had thromboembolic events had a pooled mortality rate of 23%, with thromboembolism significantly increasing the odds of mortality by as high as 74%[ 45 ].…”
Section: Discussionmentioning
confidence: 99%